Lymphatic uptake of pulmonary delivered radiolabelled solid lipid nanoparticles - Videira, MA (2015)
Lymphatic drainage plays an important role in the uptake of particulates in the respiratory system, being also associated to the spreading of lung cancer through metastasis development. In recent years solid lipid nanoparticles (SLN) have been proposed as carriers of anti-tumoural drugs, for their low toxicity and surface characteristics make them suitable for either imaging (gamma-scintigraphy) or therapy upon encapsulation of cytotoxic drugs. Assessment of inhaled radiolabelled SLN biodistribution is described in the present work. Methods : Nanoparticles (200 nm) were radiolabelled with Tc-99m using the lipophilic chelator D,L-hexamehylpropyleneamine oxime (HMPAO). Biodistribution studies were carried out following aerosolisation and administration of a Tc-99m-HMPAO-SLN suspension to a group of adult male Wistar rats. A 60 min dynamic image acquisition was performed in a gamma-camera, followed by static image collection at 30 min intervals up to 4 h postinhalation. Radiation counting was performed in organ samples, collected after the animals were sacrificed. Results : The data show an important and significant uptake of the radiolabelled SLN into the lymphatics after inhalation, and a high rate of distribution in periaortic, axillar and inguinal lymph nodes. Conclusion Results indicate that SLN could be effective colloidal carriers for lymphoscintigraphy or therapy upon pulmonary delivery.